Electrochemical pesticide sensors based on electropolymerized metallophthalocyanines - ÖZKAYA, ALİ RIZA; KOCA, ATIF (ELSEVIER SCIENCE SA, 2017)
New metallophthalocyanines (MPcs) were designed with redox active Co(II) (CoPc(ma)), Cl-Mn(III) (Cl-MnPc(ma)), and Ti(IV)O (TiOPc(ma)) metal centers and morpholin and amino bearing substituents (ma). While redox active metal centers enhanced redox activity of the complexes, redox active and electropolymerizable [2-(4-{[(1E)-(4-morpholin-4-ylphenyl)methylene]amino}phenyl)ethoxy] substituents triggered the coating of MPcs with the oxidative electropolymerizations. Voltammetry and in situ spectroelectrochemistry techniques were used for the electrochemical characterizations of MPcs. All complexes gave metal based reduction processes in addition to the Pc based processes. Moreover, all complexes were coated on GCE with the oxidations of morpholin and amino moieties of the substituents, thus redox active and conductive GCE/MPc(ma) electrodes were constructed. Modified electrodes were investigated as the potential pesticide sensors. Changing the metal center of the complexes significandy altered their sensing activities. While all complexes showed interaction abilities for chlorophyros, fenitrothion, and methomyl. GCE/CoPc(ma) electrode sensed fenitrothion with good selectivity and sensitivity. A linear range for the fenitrothion sensing with GCE/CoPc(ma) electrode was observed between 1.20 mu moldm(-3) and 42.0 mu moldm(-3) concentrations. Moreover, sensitivity and LOD of the electrode were found as 0.26 Acm(-2) M-1 and 0.46 mu moldm(-3) respectively. Although GCE/TiOPc(ma) electrode also sensed fenitrothion with a good selectivity, the linear range of this sensing was very narrow. GCE/Cl-MnPc(ma) electrode sensed all pesticides with similar voltammetric responses, thus its selectivity is poorer than the others, although it has good sensitivity for the pesticides.
Keywords: Electrochemistry; Electropolymerization; Selective pesticide sensor; Modified electrode; Metallophthalocyanine; GLASSY-CARBON ELECTRODE; COBALT PHTHALOCYANINE COMPLEXES; MOLECULARLY IMPRINTED POLYMERS; METHYL PARATHION SENSOR; SOLID-PHASE EXTRACTION; GRAPHENE OXIDE; ORGANOPHOSPHATE PESTICIDES; ELECTROCATALYTIC ACTIVITY; CLICK ELECTROCHEMISTRY; SUBSTITUTED COBALT